AI Revolution: The Legal Battle Between Indonesia and the European Union to Protect Copyright from Artificial Intelligence - Maddusila, Sitti Fatimah; Lanini, Agus; Purnamasari, Andi Intan (Faculty of Law, Hasanuddin University, 2025)
The global surge in generative Artificial Intelligence (AI) has triggered unprecedented legal complexities in copyright protection. This article examines how Indonesia and the European Union (EU) approach the challenges posed by AI driven content creation and potential copyright infringement. Through doctrinal and comparative legal analysis, this study explores regulatory frameworks, liability questions, and enforcement mechanisms in both jurisdictions. The analysis reveals that Indonesia's Copyright Law No. 28 of 2014 remains anthropocentric, lacking recognition of AI generated works and mechanisms for regulating AI training using copyrighted materials. By contrast, the EU has developed a more comprehensive approach through the EU Copyright Directive and the AI Act, which incorporates risk-based AI governance and explicit opt out rights for copyright holders. The study identifies significant regulatory asymmetries between the two jurisdictions and examines potential areas for legal development. Drawing on international frameworks such as the OECD AI Guidelines, this research suggests that Indonesia could benefit from adopting more anticipatory regulatory approaches similar to the EU's principle-based strategy. The findings indicate that proactive legal reforms are necessary to address emerging AI copyright challenges in developing legal systems. This study contributes to the growing body of comparative legal scholarship on AI governance and offers insights for policymakers navigating the intersection of artificial intelligence and intellectual property law.